Relation between pre-existing plaque size and neointimal healing in an adult porcine model of familial hypercholesterolemia. (25th November 2020) - Razzi, F; Regar, E; Dijkstra, J; Witberg, K; Ligthart, J; Ramlal, S.A; Stam, M; Krabbendam-Peters, I; Hoogendoorn, A; Duncker, D.J; Van Esch, J; Wentzel, J.J; et al.
Abstract: Background: Despite the efficacy of novel drug eluting stents (DES) in preventing restenosis, this complication still occurs, as do neo-atherosclerosis development and poor stent strut coverage that are associated with stent thrombosis. Safety and efficacy of novel coronary stents are preclinically being tested using an established porcine coronary model. However, the use of young healthy animal only allow limited conclusions to be drawn on the long-term effects, as the artieries do not reflect human pathology of advanced atherosclerosis. A key unresolved question is whether and how the presence, size and composition of pre-existing atherosclerotic plaque affect neointimal healing. Purpose: The objective of this study is to understand the role of atherosclerotic plaque in neointimal response following DES placement in a large animal model of coronary artery disease by using optical coherence tomography (OCT) analysis. Methods: The study was approved by the animal ethics committee. Familial hypercholesterolemia (FH) swine (n=6 Bretoncelles-Meishan) were given a high fat diet for 12 months to develop atherosclerosis. Stents (n=14) were implanted in n=14 coronary arteries under guidance of OCT with a stent-artery ratio of 1.1:1 at sites of atherosclerotic plaque, and animals were sacrificed after 28 days. Two types of Sirolimus eluting stents with different release profiles were implanted. Serial OCT pullbacks were taken before and after stent placement and after 28 days (follow-up), quantitatively analyzed and compared using dedicated software. The lumen area, stent area, plaque size (calculated as external elastic lamina (EEL) area - lumen area) and neointima (calculated as stent area – lumen area) were evaluated for each frame and averaged per stent. The plaque burden before stent implantation was evaluated at the same site of stent placement using coronary side branches as reference. Results: The graph shows the association between the pre-existing plaque size before stenting and neointima formation after 28 days. Surprisingly, more pre-existing plaque size resulted in less neointima (P<0.01). There was one outlier, a stent with long dissection and extensive malapposition at baseline which showed an excessive tissue response at follow-up. The response in this animal model shows similarity to human vessel response as both regions with thin neointima formation as well as poor strut coverage were observed for both stent types. Conclusion: The novel model of adult FH swine shows long-term vessel response to DES, that is similar to human response. This work shows that pre-existing atherosclerotic plaque affects the neointima after DES implantation. This insight highlights the necessity to use relevant disease models for safety and efficacy testing. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The Netherlands Organisation for Health Research and Development (ZonMw)